CO2 Activation with Formation of Uranium Carbonate Complexes in a Closed Synthetic Cycle - Waldschmidt, Pablo; Hörger, Christopher; Riedhammer, Judith; Heinemann, Frank Wilhelm; Hauser, Christina; Meyer, Karsten (Organometallics, 2020)
A closed synthetic cycle for the transformation of carbon dioxide to carbonate with a mid-valent tris(aryloxide)-ligated uranium(IV) terminal oxo complex is presented herein. Starting from the previously reported uranium(III) complex, [UIII(OArAd,Ad,Me)3], the uranium(V) terminal oxo complex, obtained by oxidation with N2O or NO, can be reduced with KC8 to yield CO2 activating anionic uranium(IV) oxo complexes [(Ad,Ad,MeArO)3UIV(O)]-. The cycle proceeds with the formation of [(Ad,Ad,MeArO)2(κ2-Ad,Ad,MeArOCO2)UIV(μ-κ1:κ2-CO3)]- upon reaction of the oxo anion with excess CO2 that adds to the terminal oxido ligand and inserts into the uranium-aryloxide bond. Treating this complex with trimethylsilyl halide eliminates both carbonates and generates, for instance, [K(2.2.2-crypt)][(Ad,Ad,MeArO)3UIV(I)2], which can ultimately be reduced with KC8 to recover the trivalent starting material, thus closing the cycle. In contrast, reaction of the 18-crown-6 stabilized U(IV) oxo analogue with CO2 yields a rare and isolable example of a uranium complex with a μ-κ1:κ2-CO3-bound carbonate weakly interacting with the [K(18-crown-6)(THF)]+ moiety; here, CO2 insertion and formation of an aryl carbonate ligand are not observed.
CRIS-Team Scopus Importer:2020-02-04